Advancing Large Interactive Surfaces for Use in the Real World. (14th June 2010) - Teichert, Jens; Herrlich, Marc; Walther-Franks, Benjamin; Schwarten, Lasse; Feige, Sebastian; Krause, Markus; Malaka, Rainer
Abstract : Interactive surfaces are only just beginning to break into the market, and they still do not offer the advanced functionality demonstrated with many lab prototypes. The path from a prototype system to a finished product for use in real-world scenarios is a long one, and many obstacles must be overcome. The design of an interactive multitouch table had to address issues like optical recognition, hardware design, and ergonomics. This paper describes in detail the construction of a large, robust multi-touch table called mrT. It will show how to solve major problems of the diffuse illumination technique and other challenges of constructing a large-screen, high-resolution, self-contained interactive multitouch surface that not only serves as a development system but can be deployed in the real-world. Additionally, to further motivate some of the design decisions, especially why the diffuse illumination technology was chosen, this paper will discuss related on-going research projects on the application side.